HAP antenna radiation pattern for providing coverage and service characteristics - Alsamhi S.H.; Rajput N.S. (My University, 2025)
The purpose of this paper is to show the most important technique in wireless communication networks that is an antenna radiation pattern. The antenna radiation pattern represents features of the antenna radiation shape in the space. The antenna radiation patterns used for determine the shape of cell size so that the difference cell sizes have difference antenna radiation patterns. The quality of coverage is depending on the cell size and QoS is depending on the coverage area which can provide via HAPs. Therefore, the antenna radiation pattern plays the most important role for HAPs coverage. The study focuses on the manner of cells or tier provided via HAP and the probability of services. If the distance between cells decreases, the number of cells increases that means the large number of tiers are used as well as the network performance will be affected by decreasing the distance between cells. Using steerable antenna is able to vary for providing constant coverage and improve the QoS. Since a steerable antenna is used on the HAP for allowance HAPs to be deployed in the different parts of the sky while the antennas boresight are still pointing at the desired coverage area. For each antenna pattern result is shown when Single HAP is considered in this study. © 2014 IEEE.